Portfolios of Real Options - Brosch, Rainer (Springer, 2017)
OR Society Award 2008! For his excellent monograph, Rainer Brosch won the German OR Society Award 2008 for outstanding theses in the field of Operations Research in September 2008. "Valuing portfolios of options embedded in investment decisions is one of the most important and challenging problems in real options and corporate finance in general. It is important for any corporation facing strategic resource allocation decisions, be it in pharma managing the pipeline of drugs, in telecom selecting a set of technological alternatives, or in venture capital or private equity investing in a portfolio of ventures. This work tackles real options decision making from a portfolio perspective head on within an overall budget constraint context in which interdependencies among optional decisions at each point in time and dynamically over time are explicitly considered. The proposed framework makes an important theoretical contribution in addressing this problem, while at the same time it can be of significant value to practicing managers in facing this admittedly complex and difficult task of evaluating, managing and optimally exercising interdependent corporate real options." Lenos Trigeorgis, Bank of Cyprus Chair Professor of Finance at the University of Cyprus and President of the Research and Consulting Firm Real Options Group in Nicosia, Cyprus.